The protective role of tissue-resident interleukin 17A–producing gamma delta T cells in Mycobacterium leprae infection - Liu, Yan; Shi, Chao; Ma, Shanshan; Ma, Yuelong; Lu, Xinyuan; Zhu, Jianyu; Yang, Degang (Frontiers in Immunology, 2022)
Mycobacterium leprae is a kind of disease-causing bacteria and results in leprosy in human. Gamma delta (γδ) T cell is a T-cell subset that is presented in both human dermis and epidermis. These cells bridge innate and adaptive immune responses and play critical roles in regulating anti-microbial defense, wound healing, and skin inflammation. Here, we investigated skin resident γδ T cells in patients with leprosy. Our data showed that γδ T cells significantly accumulated in skin lesions of leprosy patients with tuberculoid (TT) form. IL-23 can predominantly stimulate dermal γδ T cells to produce interleukin 17 (IL-17), a cytokine which may lead to disease protection. These γδ T cells expressed a specific set of surface molecules, and majority of these cells were Vδ1+. Also, IL-23 can stimulate the expansion of dermal γδ T cells expansion. Moreover, our results revealed that the transcription factor RORγt was responsible for IL-17A expression in leprosy lesion. Therefore, these data indicated that IL-23–responsive dermal γδ T cells were the major resource of IL-17A production in the skin and could be a potential target in the treatment of leprosy.